F20. THINK APP: A MOBILE APP–BASED INTERVENTION FOR ADOLESCENTS WITH FIRST-EPISODE PSYCHOSIS. (9th April 2019) - Sánchez-Gutiérrez, Teresa; Barbeito, Sara; Mayoral, María; Moreno, Miguel; Ríos- Aguilar, Sergio; Arango, Celso; Calvo, Ana
Abstract: Background: Although the use of technological advances in psychiatric treatment is relatively recent, the availability and sophistication of technologies are growing. This new therapeutic approach may provide patients with personalized, flexible, and evidence-based interventions in their communities and even in their own homes. Previous studies have shown an improvement in the access to treatment for patients with first-episode psychosis (FEP), specifically young patients, through mobile app–based interventions. The aim of this study is to develop and test the effectiveness of a mobile app–based intervention to improve community functioning in adolescents with FEP. Mobile app–based interventions could increase quality of life and disease awareness, which improve adherence to treatment and reduce the frequency of relapses and rehospitalizations in adolescents with FEP. Methods: We developed an Android and iPhone Mobile app, along with a web-based support and administration application and a cloud-based backend database, which registered fine-grain interactions between the users and the app in order to generate relevant granular data and key performance indicators and thus support a wide range of further analyses. The application was designed and developed using software engineering–based Agile Methodologies under SCRUM principles (empiric control of the development process using continuous feedback procedures). The whole mobile app functionality and its user interfaces and interactions were designed under the premise of maximizing the user experience in order to boost adherence to treatment. All the communications between the mobile app and the supporting backend were protected by means of an SSL digital certificate on the server, providing the users with end-to-end encrypted communications. We designed a randomized clinical trial to study the effectiveness of the aforementioned mobile app–based intervention for adolescents with FEP. The mobile app treatment was developed for patients with FEP aged 14–19 years recruited from Gregorio Marañón Hospital, Madrid, Spain. Results: The psychotherapy app programme is composed of 5 modules: 1) Psychoeducational module: focuses on improving patients' insight into their illness, adherence, detection and identification of prodromes, early intervention to prevent relapses, healthy lifestyles and techniques for managing anxiety, social skills, and consumption of toxic substances. In order to facilitate integration, psychoeducation will be administered through animated videos (comic-like format) of about 2–3 minutes in duration, which were made and edited by clinical experts in psychosis. 2) Module on recognition of symptoms and prevention of relapses: It has an alert system by which patients can weekly check their symptoms, cognitive performance, and emotional and behavioural circumstances. The system will return feedback with specific recommendations. 3) Problem-solving module: the participants can share their problems and ask other participants to provide possible solutions. All participants have access to a problem-solving wall. 4) Mindfulness module: we explain the concept of mindfulness and its objectives with a video and adolescents can also hear audio recordings with techniques like body scan and attention focusing (breathing and breathing) to feel better (self-compassion). 5) Contact wall module: Patients can use the wall to share their interests and experiences. The module can help to develop sociability and will bring a sense of normality, favoring activities according to age and preferences. Discussion: This is an innovative study that develop and assesses a psychological intervention through a mobile app for patients with FEP during the critical period.